BALANSE MADAM DANCE A FORM OF COLONIALISM CULTURE IN THE CUSTOM OF MARRIAGE NIAS PADANG PEOPLE - Yeni Fatrina, Novina; Stevenson, Yan (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Balanse Madam dance is one form of European-style dance that is danced in pairs. This dance is growing in Nias community in Padang city. This dance is an adoption of the dances of Europeans in the past. The adoption of Balanse Madam dance is then applied in custom ceremonies, one of which is the marriage custom of Nias Padang community. In the procession Balanse Madam dance performance reflects the culture of colonialism which later became the identity of Nias Padang community. This paper aims to reveal the cultural forms of colonialism found in the Balanse Madam dance performance. Sources of data obtained through literature study, observation, and interviews to reveal the problem. Tracking is done by looking and analyzing the forms of colonialism found in Balanse Madam dance. Writing analysis using postcolonial theory proposed by Frantz Fanon, and the theory of power relations of knowledge proposed by Michael Foucault. This paper shows the ideology behind the Nias people of Padang adopting Portuguese dances and cultural elements of Minang on Balanse Madam dance in the Nias Padang community marriage event, resulting in a culture of colonialism.